Does Philosophical Counselling Need Answers to Philosophical Questions? Polemical Review of Helena Kistelska’s Doctoral Dissertation “Philosophical counseling. Problems – theses – controversies” - Woszczyk, Agnieszka (Folia Philosophica, 2023)
The review presents the main theses of Helena Kistelska’s doctoral dissertation devoted to discussing the problem of the specificity of philosophical counselling in relation to other disciplines concerned with supporting human development. Kistelska has provided an extensive critique of philosophical counselling. She has accused it of lacking a coherent anthropological concept that could function as a theory of counselling. Such a thesis appears problematic in light of the understanding of the nature and function of philosophy. Developing a counselling practice can – as has been tried to demonstrate – be based on recognizing the dynamics of the historical process of philosophy. Such a process of searching without definitive answers provides a model for the counselling and reveals the essence of its philosophical nature.